Capital structure and firm performance in Australian service sector firms: A panel data analysis - Rafiuddin Ahmed; Rafiqul Bhuyan (Journal of Risk and Financial Management, 2020)
Using cross-sectional panel data over eleven years (2009-2019), or 1001 firm-year observations, this study examines the relationship between capital structure and firm performance of service sector firms from Australian stock market. Unlike other studies, in this study directional causalities of all performance measures were used to identify the cause of firm performance. The study finds that long-term debt dominates debt choices of Australian service sector companies. Although the finding is to some extent similar to trends in debt financed operations observed in companies in developed and developing countries, the finding is unexpected because the sectoral and institutional borrowing rules and regulations in Australia are different from those in other parts of the world.
Keywords: 330; capital structure; causality tests; firm performance; leverage; long-term debt